IMPACT OF THE RUSSIA-UKRAINE CONFLICT ON INDONESIAN COMMODITY STOCKS: A SYSTEMATIC LITERATURE REVIEW - Sanoyo, Ario Menak; Hidayat, Agus Maolana; Firmialy, Sita Deliyana (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
The Russia-Ukraine conflict has significantly impacted Indonesian commodity stocks, as revealed by a comprehensive literature review. The conflict has introduced volatility in global markets, directly affecting Indonesian stock commodity-based prices, exchange rates, and investor sentiment. While initial commodity price rises benefited Indonesian stocks, persistent volatility and market interconnectedness pose challenges. This paper employs a systematic literature review methodology, collecting, synthesizing, and analyzing numerous papers published in the last decade on a variety of topics closely related to volatility transmission issues. Based on our review of twenty-seven articles, the result of this paper's analysis underscores the importance of diversifying investments and enhancing resilience against global disruptions. The GARCH models and the Geopolitical Risk Index further emphasize Indonesian commodity stocks' susceptibility to global price fluctuations and geopolitical risks. The research concludes that the Russia-Ukraine conflict has far-reaching consequences for Indonesian stock commodity-based markets, underscoring the need for risk mitigation strategies and enhanced resilience against future geopolitical shocks.